Checklist and estimation of total number of phytoplankton species in Pari, Tidung, and Payung Islands, Indonesia - Arief Rachman (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rachman A. 2020. Checklist and estimation of total number of phytoplankton species in Pari, Tidung, and Payung Islands, Indonesia. Biodiversitas 21: 2446-2454. A checklist of phytoplankton species from an anthropogenically pressured ecosystem has become a necessity to study the marine ecosystem changes and to detect the presence of introduced species in the area. This study aimed to list and describe the phytoplankton community in the Tidung, Pari, and Payung Islands and to estimate the total number of phytoplankton species in those islands. Sampling was conducted in May 2019 in 10 sites, consisted of 5 sites around Pari Island, 1 site next to Payung Island, and 4 sites around Tidung Island. As many as 150 species of phytoplankton, consisted of 109 species of diatoms, 38 species of dinoflagellates, 3 species of cyanobacteria, were recorded in this study. However, up to 47 phytoplankton species were estimated to be missing from the current sampling effort. Three diatom species, Chaetoceros curvisetus, Chaetoceros distans, and Chaetoceros affinis were the most abundant and most common species in the studied areas. Dinoflagellates were found in low density and have limited distribution compared to diatoms. Tripos trichoceros, Tripos fusus, and Tripos macroceros were the three most common dinoflagellates in the studied islands. Several notable harmful species, such as Pseudo-nitzschia spp., Alexandrium sp., Tripos furca, Cochlodinium sp., Dinophysis miles, Prorocentrum lima, and Noctiluca scintillans, were present albeit with low cell density. However, concern on future blooms of those harmful species in the greater water regions (i.e. Seribu Island or Jakarta Bay) should be noted, as it might cause environmental damages, including a shift in species dominance and disappearance of some native phytoplankton species from the ecosystem in the future.